ANALISIS PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP RETURN SAHAM - Fathimah Mayfi; Dudi Rudianto (Universitas Mercu Buana, 2014)
Abstract: This study aims to reveal how the influence of internal factors (Total Assets Turnover / TATO, Return On Assets / ROA, Debt to Equity Ratio / DER, Current Assets / CR and Earning Per Share / EPS), and external factors (inflation, exchange rate, BI Rate , Reserves and Gross Domestic Product / GDP) on stock returns. Object of this study is the stock in the Jakarta Islamic Index (JII) in Indonesia Stock Exchange the period 2009 – 2013. Determination of the sample in this study using Shapes Multi Purpose Sampling, as for the method of analysis used is multiple linear regression model.These results indicate that the internal and external factors together have a significant influence on stock returns. While partially different effect, TATO, ROA, EPS and Exchange respectively have significant positive effect, a positive effect of foreign exchange reserves is not significant, CR and inflation has a significant negative influence, while DER, BI rate, and GDP does not have influence on stock return.Keywords: Stock Return, Internal factors, external factors, multiple linear regression.